Leber's Hereditary Optic Neuropathy: A Report on Novel mtDNA Pathogenic Variants - Peverelli, Lorenzo; Catania, Alessia; Marchet, Silvia; Ciasca, Paola; Cammarata, Gabriella; Melzi, Lisa; Bellino, Antonella; Fancellu, Roberto; Lamantea, Eleonora; Capristo, Mariantonietta; Caporali, Leonardo; La Morgia, Chiara; et al. (Frontiers in Neurology, 2021)
Leber’s hereditary optic neuropathy (LHON) is due to missense point mutations affecting mitochondrial DNA (mtDNA); 90% of cases harbor the m.3460G>A, m.11778G>A, and m.14484T>C primary mutations. Here we report and discuss 5 families with patients affected by LHON, associated with five novel mtDNA variants leading to mild oxidative phosphorylation abnormalities. Remarkably, these mtDNA variants, even without strong evidence of a deleterious effect on cell respiration, are associated with symptomatic LHON. This study remarks that in case of strong clinical suspicion of LHON, it is mandatory to analyze the whole mtDNA sequence, because new rare mtDNA pathogenic variants causing LHON are increasingly identified.